(untitled) (Seminar_BG, 2025)
This study situates itself within the field of meme culture studies, offering a critical examination of Slavic representations as depicted in the social media channels of the digital brand “Squatting Slavs in Tracksuits”. The analysis focuses on several interrelated aspects: the processes of metaphorization and exoticization of Slavic identity, its association with (post)socialist Eastern European space, and its implicit regional peripheralization. The study is unfolded on three levels: tracing the cultural and historical foundations that have shaped the perception of the Slavic world, reconstructing its contemporary landscape based on the narratives and imagery mobilized in memes, and attempting to contextualize the observed trends within broader frameworks of social and political critique. References Aleksieva, Anna. 2013. „Distsiplinata „slavistika“ – utopii i marginalizatsii“. In: Gazetić, Edisa and Kos, Dženan (eds.) Zbornik radova. Prva međunarodna znanstvena konferencija u oblasti kniževnosti i jezika. Travnik: Univerzitet Edukaciјski fakultet, 295-318. Bergson, Henri. 1996. Smehat (Ese otnosno znachenieto na komichnoto) [Le Rire : essai sur la signification du comique, (Bulgarian translation)] , prev. T. Mineva. Sofia: Izdatelstvo „Sonm“. Bourdieu, Pierre. 1998. La domination masculine. Paris: Seuil. Buchowski, Michal. 2006. “The Specter of Orientalism in Europe: From Exotic Other to Stigmatized Brother”. Anthropological Quarterly, 79 (3), 463-482. Daniel, Ondřej. 2019. “Hardbass: Intersectionality, Music, Social Media and the Far-Right on the European Periphery”. In: Appen, Ralf von and Dunkel, Mario (eds.) (Dis-)Orienting Sounds: Machtkritische Perspektiven auf populäre Musik. Bielefeld: Transcript-Verlag, 153-166. Daniel, Ondřej. 2021. “Vodka, Beer, Papirosy”. Eastern European Working‐class Cultures Mimicry in Contemporary Hardbass”. In: Kölbl, Marko and Trümpi, Fritz (eds.) Music and Democracy: Participatory Approaches, Wien: mdwPress. Dichev, Ivaylo. 2002. Ot prinadlezhnost kam identichnost. Politiki na obraza. Sofia: Lik. Đorđević, Vladimir, Suslov, Mikhail, Čejka, Marek, Mocek, Ondřej and Hrabálek, Martin. 2023. “Revisiting Pan-Slavism in the Contemporary Perspective”. Nationalities Papers, 51(1), 3-13. Götz, Еlias and Staun, Jørgen. 2022. “Why Russia attacked Ukraine: Strategic culture and radicalized narratives”. Contemporary Security Policy, 43(3), 482-497 (last seen 8.02.2024 г.). Hegel, Georg F.V. 1995. Filosofia na istoriyata. Tom II: Duhat na Evropa [Philosohpy of history, vol. II (Bulgarian translation)]. Sofia: Evrazia. Huntington, Samuel P. 1993. “The Clash of Civilizations?”. Foreign Affairs, 72(3), 22-49. Kalmar, Ivan. 2022. White But Not Quite. Central Europe’s Illiberal Revolt. Bristol: Bristol University Press. Kalmar, Ivan. 2023. “Race, Racialisation, and the East of the European Union: an Introduction”. Journal of Ethnic and Migration Studies, 49(6), 1465-1480. Kyosev, Aleksandar. 2008. „Mikrometodologia: otnoshenieto „tsentar-periferia“ kato metodologicheski problem na slavistichnata komparativistika“. V: Indigoto na Gyote. Sofia: Figura, 244-260. Lewicki, Aleksanda. 2023. “East–West Inequalities and the Ambiguous Racialisation of ‘Eastern Europeans”. Journal of Ethnic and Migration Studies, 49(6), 1481-1499. Loeb, Eli. 2020. Gopniki: Peripheral Masculinity in Post-Soviet Russia [Pomona Senior Theses. 238] (last seen 26.10.2024 г.). Mälksoo, Maria. 2010. The Politics of Becoming European. A Study of Polish and Baltic Post-Cold War Security Imaginaries. London: Routledge. Mühle, Eduard. 2018. “Inventing Slavic Unity or the Political Use of a Romantic Concept. The Case of Mikhail P. Pogodin and Joachim Lelewel”. Historia Slavorum Occidentis, 4(19), 94-118. Petrungaro, Stefano. 2023. “Pan-Slavism, its interpretative ambiguities and conflicting practices”. In: Hemstad, Ruth & Stadius, Peter (eds.) Nordic Experiences in Pan-Nationalisms. A Reappraisal and Comparison, 1840–1940. London & New York: Routledge, 260-276. Safuta, Anna. 2018. “Fifty Shades of White: Eastern Europeans’ ‘Peripheral Whiteness’ in the Context of Domestic Services Provided by Migrant Women”. Tijdschrift voor Genderstudies, 21(3), 217-231. Sojka, Aleksanda. 2020. “Liminal Europeanness: Whiteness, East-West Mobilities, and European Citizenship”. In: Kulawik, Teresa and Kravchenko, Zhanna (eds.) Borderlands in European Gender Studies Beyond the East–West Frontier. New York: Routledge, 191-210. Suslov, Mikhail. 2012. “Geographical Metanarratives in Russia and the European East: Contemporary Pan-Slavism”. Eurasian Geography and Economics, 53(5), 575-595. Ţichindeleanu, Ovidiu. 2010. “Where Are We, When We Think in Eastern Europe?”. In: Ćurlin, Ivet, Dević, Ana, Ilić, Nataša, Sabolović, Sabina, Hegyi, Dóra, László, Zsuzsa, Ziółkowska, Magdalena and Słoboda, Katarzyna (eds.) Art Always Has Its Consequences, Zagreb: WHW, 86-91. Todorova, Maria. 2009. Imagining the Balkans (Updated Edition). Oxford: Oxford University Press. Wolff, Larry. 2004. Izobretyavaneto na Iztochna Evropa. Kartata na tsivilizatsiyata v saznanieto na Prosveshtenieto [Inventing Eastern Europe. The Map of Civilization on the Mind of the Enlightenment (Bulgarian translation)], prev. R. Panayotova. Sofia: Izdatelstvo „Kralitsa Mab“. Veczán, Zoltan. 2023. “Depiction of the Balkans on Internet Memes from 9GAG”. KOME: An International Journal of Pure Communication Inquiry, 11(1), 61-94.